2020
DOI: 10.3389/fmicb.2020.00254
|View full text |Cite|
|
Sign up to set email alerts
|

Microbial Community and Its Association With Physicochemical Factors During Compost Bedding for Dairy Cows

Abstract: Overproduction of livestock manure can cause significant environmental challenges. Compost bedding (CB) is considered an effective approach for recycling the agricultural byproducts and improving the welfare of dairy cattle. During the CB preparing, the composition of microbial communities is usually altered; however, the patterns and drivers of CB microbial communities remains to be investigated. The current study aimed to explore the dynamics of bacterial and fungal communities during the various padded stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 48 publications
(56 reference statements)
4
21
0
Order By: Relevance
“…Various factors affecting the formation of compost microbial communities are known [15][16][17][18]: composting conditions, properties of the initial substrate and its microbiota, and changes in the physicochemical parameters in the course of the process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors affecting the formation of compost microbial communities are known [15][16][17][18]: composting conditions, properties of the initial substrate and its microbiota, and changes in the physicochemical parameters in the course of the process.…”
Section: Introductionmentioning
confidence: 99%
“…While relations between bacterial [16,18,19] and bacterial-fungal [15,17] consortia and environmental factors for various substrates have been considered previously, the data on the effect of high initial values of C/N and water contents on the subsequent microbial activity and diversity are scarce, as are those on their dependence on the changing ambient conditions at all stages of co-composting FW and agricultural waste.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, we support that the comparison between microbial communities should be accompanied by a composition comparison factor ( Shi et al 2020 ). The composition of microbial communities is thought to be influenced by physicochemical factors, and this way, both studies are complementary ( Sun et al 2020 ). Thus, the microbial community of mountain marshes, separated due to the topographic features of Mount Jiri, needs diverse research approaches study of physicochemical factors and diversity indicators to understand their microbial community fully.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it should be noted that the CBP bedding composition parameters are also beneficial for fungal growth [52], whereas previous studies showed a decrease in the amount of fungi during thermophilic composting processes [53]. However, microbial and molecular genetic studies on fungal growth in CBP bedding materials should also be conducted in subsequent studies including a possible influence of the fungal growth on the TAS growth and vice versa.…”
Section: Effects On the Tas Concentrations Of The Different Tas Speciesmentioning
confidence: 98%